Limnology of wastewater treatment lagoons at Pagla, Narayanganj (Bangladesh Journal of Botany, 2011)
Limnology of two wastewater treatment lagoons, (Lagoon numbers 1 and 10 are treated as L-1 and L-2, respectively) at Pagla, Narayanganj considering 15 water quality variables had been carried out for 10 months. Air and water temperature did not vary significantly. Secchi depth (Zs) showed gradual improvement from the lagoon 1 to lagoon 10 due to low loading of suspended matters. Improvement of water quality from L-1 to L-2 has also been observed in respect to alkalinity, conductivity and TDS. Similar trends were also seen for SRS and SRP. In L-1 anoxia occurred three times whereas it was absent in L-2. In the present study, improved DO prompted NO3-N and TDS concentration. However in L-2, mean values of SRP dropped by about 13% than L-1. A significant positive correlation between the density of phytoplankton and SRP in L-2 at 5% level was obtained. A total of 105 species of phytoplankton belonging to 6 different algal classes were recorded from the lagoons. Highest number of species was obtained from Chlorophyceae followed by Euglenophyceae, Bacillariophyceae, Cyanophyceae, Cryptophyceae and Dinophyceae. The population density of phytoplankton and that of zooplankton in L-1 was low compared to L-2. Higher number of genera and species occurred in L-2 than L-1. Chl a and pheopigment concentrations were also higher in L-2. Results indicated that water quality has increased in the treatment pond number 10. Key words: Limnology; Wastewater treatment lagoons; Pagla; Bangladesh DOI: http://dx.doi.org/10.3329/bjb.v40i1.7995 Bangladesh J. Bot. 40(1): 35-40, 2011 (June)